A case of conus medullaris teratoma. (January 2018) - Lekgabe, Ernest; Rogers, Te Whiti; Laidlaw, John; Lui, Elaine; Gaillard, Frank
Highlights: Spinal teratomas are usually not diagnosed radiologically due their rarity. Mature teratomas usually contain adipose tissue. Presence of findings of fat within a spinal tumour maybe a clue for teratoma. They also usually contain cystic and enhancing solid components. Abstract: In this report, we present a case of an adult patient with a mature teratoma of the conus medullaris. The patient was a 29-year-old postpartum female patient who developed unexplained urinary retention. Lumbar spine magnetic resonance imaging (MRI) examination revealed an intradural partly enhancing mixed cystic and solid lesion with intralesional intrinsic T1 hyperintense components that were suppressed on fat suppressed sequences, inseparable from the conus medullaris. Surgical resection was performed and histopathology findings were consistent with a mature teratoma. The patient made a complete recovery.